Признание в любви: стихи / Галина Микрюкова - Микрюкова Галина Савельевна ([МП "МИИЦ"], 2008)
Экземпляры: ф.1 (2008) / Инвентарный номер: zzzzzz128 / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: М 59 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5